2010
DOI: 10.1039/c000114g
|View full text |Cite
|
Sign up to set email alerts
|

Observation of pH-, solvent-, spin-, and excitation-dependent blue photoluminescence from carbon nanoparticles

Abstract: Highly blue luminescent carbon nanoparticles with photo-luminescence quantum yields of 31.6%-40.6% were prepared by a one-step pyrolytic route from ethylenediamine-tetraacetic acid salts and a unique emission that is strongly dependent on pH, solvent, spin, and excitation wavelength was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
386
7
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(416 citation statements)
references
References 16 publications
18
386
7
5
Order By: Relevance
“…At 470 nm ≤ λex ≤ 540 nm, the emission peak continuously shifts from 527 to 571 nm. This excita- tion-dependent PL behavior is similar to that observed for other luminescent carbon nanoparticles [46,47]. At λex < 470 nm, the position of the emission peak remains almost unchanged and an even blue-shift is noticed from 420 to 430 nm.…”
Section: Spectroscopic Properties Most Of the Previous Studies On Cqdsupporting
confidence: 64%
“…At 470 nm ≤ λex ≤ 540 nm, the emission peak continuously shifts from 527 to 571 nm. This excita- tion-dependent PL behavior is similar to that observed for other luminescent carbon nanoparticles [46,47]. At λex < 470 nm, the position of the emission peak remains almost unchanged and an even blue-shift is noticed from 420 to 430 nm.…”
Section: Spectroscopic Properties Most Of the Previous Studies On Cqdsupporting
confidence: 64%
“…This is quite different from that of the C-dots derived from candle soot, which fluorescence intensity decreased significantly (by 40-89%) upon changing from a neutral to either an acidic or a basic solution [26]. Even though this mechanism is not fully understood, the pH effect indicates that the fluorescent species in the dots have nearly neutral sites because of the fluorescence intensity not being significant quenched in the acidic media [31]. The radiative recombination of the energy-trapping sites on the C-dots surface is not significantly affected with varying the pH value from alkaline to acidic, which corresponds with the protonation of the carboxyl groups of the CDs.…”
Section: Resultsmentioning
confidence: 70%
“…As we know that the luminescence mechanism of the CDs was still not clearly understood, the proposed reason might be the rediative recombination [7]. The green luminescence of the CDs might be attributed to surface energy traps [7], and the blue emission of the C-dots might be attributed to zig-zag sites [31,32] due to the grapheme molecules embedded in the C-dots.…”
Section: Resultsmentioning
confidence: 99%
“…It is important that ethanol addition has no effect on the PL peak. It is often observed that there is a small shift of the PL maxima peak position with respect to the varying environment of the CDs which may include pH, solvent and/or other organic molecules [15,29,30]. The quantum yield (QY) of the CDs in solution was about 40% while embedded in the Silica/F127 matrix the QY is slightly increased to 50 %.…”
Section: Resultsmentioning
confidence: 99%